Educational Innovation. A Documentary Analysis - Seminario-Hurtado, Nuccia (2024)
The objective of this article is to analyze the scientific literature regarding educational innovation in a theorical context. To this end, the research had a qualitative approach of documentary analysis type. We worked with a unit of analysis of 17 documents; on one hand, 4 dissertations, and, on the other hand, 13 articles indexed in Scopus that met the three exclusioncriteria proposed in the research: i) type of publication, ii) temporality criterion and iii) language criterion. The study concluded that educational innovation is a set of processes that, through new practices, seek improvement in institutional management, teaching performance and the learningteaching process of students, with the purpose of transforming and impacting positively, the education sector.